2014
DOI: 10.1063/1.4861636
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of femtosecond laser induced active channel waveguides in lithium fluoride crystals

Abstract: We successfully realized broad-band light-emitting color center waveguides buried in LiF crystals by using femtosecond laser pulses. The characterization of the waveguides was performed by optical microscopy, photoluminescence spectra, loss measurements and near-field profiling. The experimental results show that the direct-writing fabrication process induces low-index contrast active channel waveguides: their wavelength-dependent refractive index changes, estimated from 10(-3) to 10(-4) depending on the writi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In the work of Sotillo 7 , the development of optical techniques to inscribe optical waveguides and other micro-structures in diamond is reviewed. The physical mechanism for fsLW in glasses 5–8 differs from that in crystals 9,10 , with a local refractive index increase in the former, and an index decrease in the latter.…”
Section: Introductionmentioning
confidence: 91%
“…In the work of Sotillo 7 , the development of optical techniques to inscribe optical waveguides and other micro-structures in diamond is reviewed. The physical mechanism for fsLW in glasses 5–8 differs from that in crystals 9,10 , with a local refractive index increase in the former, and an index decrease in the latter.…”
Section: Introductionmentioning
confidence: 91%
“…Studies on the equilibrium dynamics of the aggregate centers showed the possibility of provide a selective depopulation of one of the species [21]. The efficiency of the lithium fluoride optical pumping cycle allows a number of applications such as waveguides [22]- [27], color center lasers [28], including those with distributed feedback [29] periodic photorefractive structures [30] and even radiation detectors [31]. Radiation detectors are particularly interesting for imaging with confocal laser-scanning-microscopy using fluorescent excitation, allowing better resolution than conventional techniques and greater applicability in samples.…”
Section: Effects Of Birefringence On the Electromagnetic Guidance Of mentioning
confidence: 99%
“…Adequate modifications in the parameters of the writing technique allowed the fabrication of Bragg waveguides in LiF crystals with femtosecond laser pulses. Several works focused on the study of the Bragg waveguide dimensions and the associated refractive index variations [25], the measurement of light propagation parameters in the range from 458 nm to 1550 nm [26]- [27] and the production of LiF crystal waveguide lasers [24], [33].…”
Section: Effects Of Birefringence On the Electromagnetic Guidance Of mentioning
confidence: 99%
“…Recently, the writing of fs induced waveguides in Lithium Fluoride and several of their characteristics were reported [15,16], the observed transversal cross section is also not regular, as can be seen in Fig. 1, which shows fluorescence confocal laser microscopy images of the transverse plane from (a) the side face and (b to d) from the bulk of a lithium fluoride crystal, where several optical waveguides were recorded by a femtosecond pulsed laser.…”
mentioning
confidence: 99%
“…1, which shows fluorescence confocal laser microscopy images of the transverse plane from (a) the side face and (b to d) from the bulk of a lithium fluoride crystal, where several optical waveguides were recorded by a femtosecond pulsed laser. The visible fluorescence is due to the local formation of laser-active aggregate color-centers in the LiF matrix [15,16]. Figure 1(e) shows the NFP measured from one waveguide when using an ASE source, with central wavelength at 1550 nm, to launch light into the waveguide.…”
mentioning
confidence: 99%